Seven-Year Analysis of Microbial Keratitis Tendency at an Ophthalmology Department in Poland: A Single-Center Study - Klaudia Ulfik; Sławomir Teper; Michał Dembski; Anna Nowińska; Ewa Wróblewska-Czajka; Edward Wylęgała (Journal of Ophthalmology)
This study aimed to analyze the frequency, drug susceptibility, and drug resistance of pathogens causing microbial keratitis (a corneal inflammation) in the Clinical Department of Ophthalmology, Medical University of Silesia, Katowice. Despite intensive treatment, severe inflammation causes irreversible blindness in ∼7% of cases and eye loss (evisceration or enucleation of the eyeball) in ∼1% of cases at our hospital. The choice of a targeted drug depends on the culture result and drug resistance of the microorganism. This was a retrospective observation study. Conjunctival swabs and corneal scrapes were collected between January 1, 2013, and December 31, 2019, in the tertiary reference center for keratitis. The collected data included the type of material received, culture result, and antimicrobial susceptibilities. Of the 2482 samples analyzed, 679 were positive and 1803 were negative. Of the total pathogens isolated, 69.9% were Gram-positive bacteria, 20.8% were Gram-negative bacteria, and 7.1% were fungi. A significant increase in the number of Gram-positive methicillin-resistant Staphylococcus aureus and a partial increase in the number of Gram-negative beta-lactams-resistant bacteria were observed. All fungal species were sensitive to amphotericin B, 82.81% were sensitive to voriconazole, and 56.25% were sensitive to fluconazole. Dual drug therapy (levofloxacin and tobramycin) was the first-line treatment. Drug susceptibility testing of the cultured microorganisms is necessary to initiate targeted treatment. Increased drug resistance was observed in this study. In the present study, most bacteria were sensitive to fluoroquinolones. Ciprofloxacin therapy remains the recommended empirical treatment in microbial keratitis. According to our study, voriconazole remains a first-line antifungal drug, when a fungal infection is suspected.